2012
DOI: 10.1371/journal.pone.0030333
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Economic Evaluations of Preparedness Strategies and Interventions against Influenza Pandemics

Abstract: BackgroundAlthough public health guidelines have implications for resource allocation, these issues were not explicitly considered in previous WHO pandemic preparedness and response guidance. In order to ensure a thorough and informed revision of this guidance following the H1N1 2009 pandemic, a systematic review of published and unpublished economic evaluations of preparedness strategies and interventions against influenza pandemics was conducted.MethodsThe search was performed in September 2011 using 10 elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 47 publications
1
54
0
Order By: Relevance
“…Influenza A, a zoonotic disease, represents a substantial public health burden, especially in the case of epidemic or pandemic outbreaks [1, 2]. Influenza A virus subtypes, found naturally in aquatic birds, are identified according to their surface antigens: hemagglutinin (HA) and neuraminidase (NA).…”
Section: Glycans As Host Receptors For Influenza a Virusesmentioning
confidence: 99%
“…Influenza A, a zoonotic disease, represents a substantial public health burden, especially in the case of epidemic or pandemic outbreaks [1, 2]. Influenza A virus subtypes, found naturally in aquatic birds, are identified according to their surface antigens: hemagglutinin (HA) and neuraminidase (NA).…”
Section: Glycans As Host Receptors For Influenza a Virusesmentioning
confidence: 99%
“…Among the very few reviews on relevant topics our search retrieved, most of them have focused on a specific disease area, geographic location, non low and middle-income country (LMIC) region, or type of intervention. [13][14][15][16][17] Other reviews have also focused mainly on examining individual behaviors within affected groups or populations. 18,19 Finally, most reviews 20,21 focus on actual mitigation measures (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent systematic review, Pérez Velasco et al identified 44 economic evaluations of pandemic preparedness strategies. 3 Although the first of these was published in 1999, the majority (75%) were published from 2009 onwards. Pérez Velasco et al evaluated these 44 studies against a checklist of standard practices in the field of economic evaluation, but their stated aim was to summarize the literature and offer policy recommendations rather than to examine methodological approaches.…”
Section: Introductionmentioning
confidence: 99%